PENGARUH MEDIA TANAM SERBUK GERGAJI DAN COCOPEAT TERHADAP PERTUMBUHAN DAUN PADA PENCANGKOKAN TANAMAN MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl.) - Suci Syafputri; Vauzia; Irma Leilani Eka Putri; Filza Yulina Ade (Universitas Cokroaminoto Palopo, 2026)
The mahkota dewa plant (Phaleria macrocarpa (Scheff.) Boerl.) plant is a medicinal plant with high economic and pharmacological value, so effective propagation techniques are needed to increase its production. One method used is grafting, the success of which is influenced by the planting medium. Based on this, a study was conducted on the effect of sawdust and cocopeat growing media on leaf growth in grafting crown of the gods plant. The study was conducted in January 2026 in the Lubuk Minturun area of ​​Padang City. This study used a Completely Randomized Design (CRD) with three treatments: soil (P0), sawdust (P1), and cocopeat (P2), each with six replications, resulting in 18 experimental units. Observed parameters included leaf number and leaf dry weight. Data were analyzed using analysis of variance (ANOVA). The results showed that the planting medium used had no significant effect on leaf number or dry weight.